Changes in women’s empowerment in the household, women’s diet diversity, and their relationship against the background of COVID-19 in Southern Bangladesh - Lecoutere, Els; Van den Berg, Marrit; de Brauw, Alan (International Food Policy Research Institute, 2021)
The COVID-19 pandemic in Bangladesh, associated public health measures, and people’s responses to these measures are projected to have caused job losses among women, who tend to be in more precarious jobs, a decline in women’s empowerment and reduced diet diversity among women. Using a November 2020 telephone survey to re-interview adult women respondents of a November 2019 in-person survey, we test the way and the extent to which women’s employment outside their homes, women’s decision-making power with regard to income use and food purchases, and women’s diet diversity in rural Patuakhali and Faridpur districts changed over the year partly marked by the COVID-19 pandemic. We further examine the relationship between change in women’s empowerment and change in women’s outside employment, and the relationship between change in women’s diet diversity and change in women’s empowerment. Contrary to expectations, we find more women found, rather than lost, jobs over the past year. The chance that women gained outside employment was 12.2 percent, while the chance they lost employment was 3.5 percent. However, we observe a negative trend in women’s involvement in food purchase decisions in their households. Changes in women’s decision-making power over food purchases are not statistically related to change in women’s outside employment. Gaining employment outside the home is associated with a decrease in women’s autonomy over the use of household income. Contrary to expectations, we find the number of food groups consumed by women increased over the year with COVID-19. The chance that women gained achievement of minimum diet diversity over the year is 38 percent; the chance they lost it 11.5 percent; the chance it did not change is 50.5 percent. Change in women’s diet diversity is positively related with change in women’s decision-making power over food purchases but negatively with change in women’s autonomy over income use.